Quantitative Estimation of Insulin Sensitivity in Type 1 Diabetic Subjects Wearing a Sensor-Augmented Insulin Pump - Schiavon, Michele; Dalla Man, Chiara; Kudva, Yogish C.; Basu, Ananda; Cobelli, Claudio (Diabetes care, 2014)
The goal was to develop a new index of insulin sensitivity in patients with type 1 diabetes estimated from continuous glucose monitoring (CGM) and subcutaneous insulin delivery data under carefully controlled conditions. The database consists of 12 subjects with type 1 diabetes, studied during breakfast, lunch, and dinner, in a clinical research unit, wearing both subcutaneous insulin pump and CGM device. Frequent blood samples were drawn for measurements of plasma glucose and insulin concentrations in order to estimate insulin sensitivity with the oral minimal model (SI(MM)). The new index of insulin sensitivity (SI(SP)) was calculated with a simple algebraic formula for each meal, using only CGM and insulin pump data and compared with SI(MM). SI(SP) was well correlated with SI(MM) (r = 0.825; P < 10(-8)), and diurnal pattern was also similar to SI(MM). A novel method for estimating insulin sensitivity in subjects with type 1 diabetes on sensor-augmented insulin pump therapy has been presented. This new index correlates well with the reference oral minimal model estimate of insulin sensitivity. The knowledge of patient-specific insulin sensitivity and its diurnal variation can help in optimizing insulin therapy in type 1 diabetes and could also inform next-generation closed-loop control systems.